Efficacy of left atrial low-voltage area-guided catheter ablation of atrial fibrillation: An updated systematic review and meta-analysis - Zhou, Yaqiong; Zhang, Huamin; Yan, Peng; Zhou, Peng; Wang, Peijian; Li, Xiaoping (Frontiers in Cardiovascular Medicine, 2022)
Aims: This study aimed to evaluate the efficacy of low-voltage area (LVA)-guided substrate modification catheter ablation in patients with atrial fibrillation (AF). Methods: Systematic searches of the PubMed, EMBASE, and Cochrane databases were performed from inception to July 2022 for all available studies. The effect estimates were combined with the Mantel–Haenszel random-effects model. Subgroup analyses, sensitivity analysis and meta-regression were conducted to explore the sources of statistical heterogeneity. Results: A total of 16 studies involving 1931 subjects (mean age: 61±10 years, 69% male) were identified. All studies included patients with paroxysmal AF, non-paroxysmal AF, or both. At a mean follow-up of 18.9 months, patients who underwent LVA-guided substrate modification ablation had significantly higher freedom from all-atrial tachycardia recurrence than patients who underwent control ablation (67.6% vs. 48.9%, risk ratios [RR] 0.66, 95% confidence interval [CI] 0.57-0.76, P<0.001), with 34% relative risk and 18.7% absolute risk reductions in all-atrial tachycardia recurrence. Subgroup analysis based on AF types demonstrated that the decreased risk of all-atrial tachycardia recurrence was present predominantly in non-paroxysmal AF than paroxysmal AF (RR 0.62, 95% CI 0.53-0.73 vs. RR 0.82, 95% CI 0.67-1.0). Conclusion: LVA-guided substrate modification ablation combined with PVI appears to have a significant beneficial effect of improving freedom from all-atrial tachycardia recurrence, especially in patients with non-paroxysmal AF.